A Poet's Perspective: The Beauty of Life Reflected in Boris Pasternak’s Later Works - Supian, Supian; Prikhoda, Ekaterina; Dallyono, Ruswan; Ladinata, Ladinata (POETIKA, 2024)
This article examines the relationship between Boris Pasternak’s life and his artistic expression through his later poems. Following Wellek & Warren’s (1954) qualitative biographical analysis of Pasternak, which is basically associated with the qualitative method, we examined his personal narrative that contributed to the formation of his poetic voice. Data were taken from Pasternak’s later poems, namely “When It Clears Up” (1956-1959)–to Pasternak’s life stories, mainly taken from Pasternak’s biography by Hingley (2021) and the compilations of his letters to his family and friends (Slater, 2010). This study revealed that the events in his life greatly influenced his creation because they became the key motif of his narrative. The death of his brother and sister was influential in his studies of mortality and death, including grief. Peredelkino was a small village, and his longer period of stay helped him to have a chance to escape in nature and to experience loneliness to the greatest extent. In addition, his poetic work carries the features left by his teachers Alexander Skryabin and Hermann Cohen. To make up for the criticism of Belyi, whom he met in the summer of 1911, Skryabin offered Pasternak the aesthetic ideals of the latter work, developing the principles of poetry. Thus, in addition to recommending for Pasternak’s literary reading material other authors’ opinions on various philosophical issues, Cohen’s philosophic teaching enriched Pasternak’s outlook on the world and launched the latter on his poetic path. Understanding the specifics of Pasternak’s late poems provides knowledge of his life shots and the interconnectedness between his experiences and creation. The novelty of this study is reflected in the integration of a biographical analysis with a poetic interpretation. Such an approach uniquely combines the qualitative biographical analysis with a close reading of Pasternak’s later poems.